Neuroprotective Effect of Vanda roxburghii Extract in Endothelin-1 (et-1) Induced Hippocampal Ischemic Damage and Ameliorate Cognitive Deficit - Mundugaru, Ravi; Sharma, Sukrant; Sivanesan, Senthilkumar; Thangarajan, Rajesh; Naik, Pundalik Rama; Raju, Nagesh; Alfarhan, Ahmed; Rajagopal, Rajakrishnan; AlMunqedhi, Bander (Indian Journal of Pharmaceutical Education and Research, 2020)
Introduction: The concept of neuroprotection gaining considerable interest in search for novel therapy that has potential to preserve brain tissues and improve cognitive functions in ischemic brain damage. In the present study we evaluated the neuroprotective efficacy of hydro alcoholic extract of Vanda roxburghii in experimental models of ischemic hippocampal injury in rats. Materials and Methods: Ischemic hippocampal injury was induced by single intra-hippocampal injection of Endothelin-1 (80μM) using stereotaxic instrument. Following ischemic hippocampal damage, hydro alcoholic extract of Vanda roxburghii (HAVR) (200 and 400mg/kg) was administered orally, once in a day for 14 consecutive days. Results and Discussion: The Morris water maze, Actophotometer and Open field behavioral test results showed significant cognitive deficit after ischemic hippocampal damage, however the repeated administration of HAVR at higher dose level for 14 consecutive days attenuated the cognitive deficits to a significant level. The histopathological examination of CA1 and CA3 regions of hippocampus revealed the loss of normal pyramidal cells and degenerative changes with shrunken, hyperdensed soma with pyknotic nuclei, however HAVR treatment at both dose levels significantly attenuated the observed qualitative changes. HAVR treatment showed significant anti-oxidant properties by inhibiting lipid peroxidation in ischemic condition as well as restoration of glutathione peroxidase enzymes to significant level. Conclusion: The study concludes that V. roxburghii extract and its constituents have neuroprotective potentials in ischemic hippocampal injury.
Keywords: Stereotaxic; Hippocampus; Pyramidal cells; Morris water Maze; Lipid; peroxidation